2011
DOI: 10.1097/mnh.0b013e328348bcc7
|View full text |Cite
|
Sign up to set email alerts
|

Physiological regulation of epithelial sodium channel by proteolysis

Abstract: The discovery of serine protease-mediated activation of renal ENaC in physiological and pathophysiological conditions opens the way for new understanding of the pathogenesis of proteinuric sodium retention, which may involve plasmin and present several potential new drug targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 64 publications
2
26
0
Order By: Relevance
“…33 While direct ENaC channel activity was not assessed in this study, we did assess cleavage and abundance of the alpha and gamma subunits. Cleavage is well established to activate channels in vitro and in vivo, 25, 26 evident as greater amiloride sensitive natriuresis. 27 …”
Section: Discussionmentioning
confidence: 99%
“…33 While direct ENaC channel activity was not assessed in this study, we did assess cleavage and abundance of the alpha and gamma subunits. Cleavage is well established to activate channels in vitro and in vivo, 25, 26 evident as greater amiloride sensitive natriuresis. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone can increase renal ENaC activity by increasing a-subunit expression and increasing cell surface localization. The aENaC and gENaC subunits can also be activated via protease-dependent removal of inhibitory peptides, and the cleaved forms increase 16,20 Other potential explanations for the increased abundance of this gENaC [112][113][114][115][116][117][118][119][120][121][122] peptide include increased absolute gENaC production and urinary excretion, or more efficient trypsin digestion after gENaC is proteolytically cleaved in vivo. Although this gENaC [112][113][114][115][116][117][118][119][120][121][122] biomarker may be useful in humans, this peptide region is variable across species, so an analogous peptide sequence would be needed in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with protein-rich urine from both nephrotic rats and patients have shown a stimulation of ENaC currents in vitro that was attributed to occurrence of the serine protease plasmin in the urine (4,5). It is an emerging concept that serine proteases contribute to ENaC regulation by cleaving specific sites in the extracellular domains of the a-and g-subunits (6)(7)(8)(9)(10), resulting in the release of inhibitory peptides and activation of the channel (11)(12)(13). Proteolytic activation of ENaC by serine proteases as shown in native renal tissue (14) is enhanced by low-salt diet or aldosterone infusion (15) and might involve membrane-anchored prostasin (16) and/or tissue (urinary) kallikreins (17).…”
Section: Introductionmentioning
confidence: 99%
“…Proteolytic activation of ENaC by serine proteases as shown in native renal tissue (14) is enhanced by low-salt diet or aldosterone infusion (15) and might involve membrane-anchored prostasin (16) and/or tissue (urinary) kallikreins (17). Under pathophysiologic conditions of proteinuria, ENaC is thought to be aberrantly activated by plasmin that arises from filtered plasminogen and conversion by the tubular urokinase-type plasminogen activator (4,6).…”
Section: Introductionmentioning
confidence: 99%